ANALYSIS OF THE EFFECT OF ECONOMIC GROWTH, PERCENTAGE OF POOR PEOPLE, AND OPEN UNEMPLOYMENT RATE ON THE HUMAN DEVELOPMENT INDEX IN EAST KALIMANTAN PROVINCE - Mardiko, Tri Fahmi; Rospida, Lela (Jurnal Ekonomi, 2023)
This study aims to identify the factors that influence the human development index in East Kalimantan province during the period 2015 to 2022. The research findings were evaluated using the Fixed Effects Model (FEM) panel data test conducted with Eviews 13 software. The dataset consists of secondary data collected from 10 districts/cities in East Kalimantan, both time series and cross-sectional data. The research findings show that the economic growth variable has a positive and significant influence on the human development index. In contrast, the poverty rate variable has a negative and significant influence on the human development index. In addition, the open unemployment rate has a negative and significant impact on the Human Development Index in East Kalimantan Province.